Development of Android-Based Electronic Module on Biotechnology Material to Support Online Learning - Dewi Jumiarni; Rendi Zulni Eka Putri; Rambat Nur Sasongko; Endang Widi Winarni; Eko Risdianto (Edukasi Islami : Jurnal Pendidikan Islam, 2022)
This study produced an android-based e-module for Basic Biology course on Biotechnology material to support online learning. This study is a research and development using ADDIE model. Data were collected by using questionnaires and interviews, while the data analysis technique using qualitative and quantitative descriptive. The developed e-module was then validated by validators from teaching material experts. The readability test was carried out to 30 students. The results of this study revealed that the android-based e-module on Biotechnology material was valid. While the student readability test assessment revealed that the medium was very good. Thus, the e-module developed is feasible implemented in class for online learning.